A Lyapunov optimization approach to energy-efficient content delivery networks. (March 2020) - Goudarzi, Pejman; Mousavinejad, Mahmoud
A content delivery network (CDN) supports fast growing services (such as streaming media) for end users and uses request a routing algorithm to enhance the users' perceived quality of experience (QoE). This working process can increase the power consumption and eventually the operational cost of the CDN system substantially. In addition, a smart grid facilitates real-time electricity pricing for the consumers as well as the integration of green energy resources into the electrical grid for improving the system efficiency. In this paper, we first take into account these key functionalities of a smart grid to propose a real-time energy management algorithm for reducing the operational cost within a CDN cluster. We then define the proposed stochastic optimization algorithm for jointly optimizing the energy cost and perceived quality within a CDN system based on the popular Lyapunov-drift methodology. Numerical results are presented to evaluate and validate the aforementioned solution. The obtained results indicate large operational and energy cost savings for a single CDN or more than one CDN providers over a conventional method that only optimizes the users' perceived QoE.